Grandma's Treasure - Olatunde, Dunni (Nigeria, 2020)
The Ilesanmitwins are back at their grandparents' house for Christmas, and it doesn't take long for another mystery to find them. This time, it involves their grandmother's prized necklace. Stolen during her birthday party, the list of suspects is daunting, and the twins and their cousins might just be in over their heads...
Keywords: Adventure; Juvenile Fiction; Mystery & Crime